Evaluation and prediction of material fatigue characteristics under impact loads: review and prospects. Issue 2 (17th January 2022) - Liu, Xintian; Wu, Que; Su, Shengchao; Wang, Yansong
Abstract : Purpose: The properties of materials under impact load are introduced in terms of metal, nonmetallic materials and composite materials. And the application of impact load research in biological fields is also mentioned. The current hot research topics and achievements in this field are summarized. In addition, some problems in theoretical modeling and testing of the mechanical properties of materials are discussed. Design/methodology/approach: The situation of materials under impact load is of great significance to show the mechanical performance. The performance of various materials under impact load is different, and there are many research methods. It is affected by some kinds of factors, such as the temperature, the gap and the speed of load. Findings: The research on mechanical properties of materials under impact load has the characteristics as fellow. It is difficult to build the theoretical model, verify by experiment and analyze the data accumulation. Originality/value: This review provides a reference for further study of material properties.